And Then There Were Ten: Equity and Adequacy of New York City Schools after Recentralization - Nicola A. Alexander (Educational Considerations, 2013)
New York City has the largest public education system in the United States, serving over 1.1 million students in 1,700 schools. Given its size, the city school system is a good place to explore the potential associations between various educational reforms and questions of adequacy and fairness.
Keywords: disciplines; equity; education; research; decentralization; recentralization; elementary school